Customer Loyalty Analysis on Valuation of Price, Location, Facilities, and Service Standards with the Structural Equation Modeling Method - Partial Least Squares (SEM-PLS) - Poniman; Thoriq , Fitrah; Mandati, Sri Amalia; Batutah, Moh Arif; Utomo, Yitno (Tibuana, 2025)
Abstract - The world of business and industry, including the culinary industry, is rapidly developing in this modern era. Business owners have to compete in an increasingly tight situation. Compared to previous studies, this study is newer because it uses more variables. This quantitative study used 60 samples. SmartPLS software version 3.0 is used to perform the analysis with SEM. Outer model, inner model, mediation, and hypothesis tests are carried out. The results of the validity test show that the data is valid. The filling factor value is more than 0.7 and the AVE value is more than 0.5. In contrast, reliability tests show the reliability values of composites and Cronbach's alpha, which are also greater than 0.7 and are considered reliable. From the histothesis analysis carried out, it can be concluded that; The consumer choice variable has a significant positive impact on customer loyalty, the facility and infrastructure variable has a significant positive impact on consumer choice, the facility and infrastructure variable has a significant positive impact on customer loyalty, the business location variable has a significant positive impact on consumer choice, the business location variable has a negative impact on customer loyalty, the price assessment variable has an impact negative on consumer choice, the price assessment variable has a significant positive impact on customer loyalty, the service standard variable has a significant negative impact on customer choice and customer loyalty. These results show the importance of paying attention to these variables in business strategy.